STRATEGI PEMASARAN KUE DI “TOKO KUE SUVENIR” PONDOK KELAPA JAKARTA TIMUR: MARKETING STRATEGYCAKE AT THE “SUVENIR CAKE SHOP” KELAPA POINT, EAST JAKARTA CITY - Lutfiadi, Ridwan; Rahmanto, M Ikhwan; Dwihatmojogeni, Cesarjati (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2023)
The study aims to identify internal and external environment, to know the position of the firm, and to determine priority with alternative marketing strategy. The analytical method used is IFE and EFE matrices, IE matrices, SWOT matrices and QSPM matrices. The results based on IFE matrices has a greatest strength is strategic store location and the worst weakness is less adequate parking space. In EFE matrices,the greatest opportunity is many requests for the cake and the worst threat is facilities at the other shop are better. Then, IFE matrices and EFE matrices combined in IE matrices show that the Suvenir Cake store is at sel V. At this position, the right strategy is strategy of keeping and maintaining. The preparation of alternative strategy is used SWOT matrices. Based on QSPM analysis there are three strategy with highest score. the main strategy that can be executed first is maintain and improve quality and service, improve good business governance, cooperate with suppliers and purchase equipment to increase customer satisfaction.